Consumers’ Knowledge, Attitude and Practice Towards Medicinal and Aromatic Plants in the East Coast Economic Region - Arumugam, Nalini; Nurul Imanina, Kamal Bahri (2019)
This study aims to assess the knowledge,attitude and practices of consumers towards medicinal and aromatic plant (MAP).MAPs have been utilized as an alternative medicine for quite a long time based on indigenous knowledge inherited from the older generation. However, there is a lack of documentation concerning the level of knowledge,attitude and practice of consumers specifically in the East Coast Economic Region (ECER). Knowledge, attitude and practices have an impact on the consumption of medicinal and aromatic plants. Descriptive analysis, Pearson correlation, multiple regression analysis and factor analysis will be employed to analyse the data. Finding from this study will benefit the consumers, producers and academic researchers.